The role of a leader in managing mutigenerational virtual teams - Koszyk, Beata (Journal of Management and Financial Sciences, 2025)
The today's workplace rapidly evolves, with the increasing role of virtual teams which reshape traditional team settings. At the same time, labor market becomes more generationally diverse, with Baby Boomers, Generation X, Generation Y (Millennials), and Generation Z working side by side, each bringing unique perspectives, expectations, and work styles. In this dynamically changing environment, effective leadership is more critical than ever. The purpose of the article is to present the results of a survey conducted in April 2024 on the expectations of employees from different generations regarding the expected and the current level of competences of virtual team leaders. On the basis of the research, it was found that each generation have different expectations in terms of competences of a virtual team leader. Findings also show that there is a discrepancy between expectations and the current level of competences of virtual team leader.